Analogue trauma results in enhanced encoding of threat information at the expense of neutral information. - Krans, J; Reinecke, A; de Jong, P; Näring, G; Becker, E (2012)
This study investigated whether trauma-related stimuli are preferentially processed at the expense of ongoing processing of neutral stimuli. Participants in the experimental group viewed negative pictures (Trauma) as an analogue trauma induction. Participants in the control group viewed visually similar neutral pictures (Neutral Match). In a Rapid Serial Visual Presentation (RSVP) task participants identified two target pictures. The first target (T1) was a neutral picture, whereas the second target (T2) was a familiar negative or neutral picture or a new neutral or negative picture. In line with hypotheses, only participants in the experimental group showed preferential processing of Trauma pictures. In the experimental group, negative T2 impaired the identification of (neutral) T1 if the T2 immediately followed the T1 in the RSVP stream. The results are consistent with a processing priority of trauma-related information, apparently at the expense of the ongoing processing of neutral information.